Erialsr makeup artist service business development strategy - Ultimarchya, Debra; Jahroh, Siti; Hannan, Sufrin (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of the study is to identify core competencies through internal and external factors, analyze internal and exterior environmental factors that affect the business model of Erialsr Makeup Artist services, and formulate priority strategies for Erial's make-up artist service business. The research used a qualitative descriptive approach method. The primary data were obtained from questionnaires and in-depth interviews selected by purposive sampling. The results of this study show a number of factors of the internal environment of management, namely, market penetration, market development, and product development. The key factors in the form of (6) strengths and (6) weaknesses and (5) opportunities and threats, are obtained. The strategies that can be applied by the internal management are market penetration (PT), market development (PD), product development (SP), and market development strategies. The main strategies are making a PT, diversifying online makeup course programs that can reach various market segments in various cities in Indonesia and diversifying offline makeup course program materials that have not yet appeared on the market, registering HAKI for products owned, and obtaining professional certification to increase customer confidence in services and teaching.